The Crucial Role of Local Adaptation in the Conservation of the Giant Panda Under Climate Change - Shulin Yu; Muyang Lu; Renqiang Li; Lehua Ning; Di Zhu; Zhaosheng Wang; Jinli Huang; Jingyong Zhang; Hui Wen; Weichao Zheng; Pan Wang; Zhen Xu; et al. (Global Change Biology, 2026)
Climate change‐driven conservation strategies commonly project habitat availability but may not account for local adaptation among populations of the same species, which can influence prediction accuracy. Using the giant panda ( Ailuropoda melanoleuca ) as a case study, we developed a regional‐scale species distribution model (SDM) and 33 population‐specific local models to assess niche divergence and climate‐induced habitat shifts (current vs. 2080–2100, SSP2‐4.5). Comparisons between the two model scales, validated against observed habitat distributions, revealed clear differences in predicted habitat range, area, quality, and fragmentation among local populations. Specifically, regional‐scale models predicted lower climate threats for 15 local populations, higher threats for 10, and did not identify suitable habitats for 8 populations, particularly those that were smaller and more isolated. These findings highlight the importance of incorporating population‐specific climatic niche differentiation into conservation planning to improve the reliability of climate impact assessments and to guide population‐level strategies for biodiversity conservation under future climate change.